PHOTODEGRADATION OF 1, 4-DIHYDROPYRIDINE ANTIHYPERTENSIVE DRUGS: AN UPDATED REVIEW - Luca, Michele De; Ioele, Giuseppina; Spatari, Claudia; Ragno, Gaetano (International Journal of Pharmacy and Pharmaceutical Sciences, 2018)
1, 4-dihydropyridine calcium channels blockers (DHPs) are the most commonly used antihypertensive drugs. Unfortunately, these compounds have a significant degradability to light. The oxidation to the pyridine derivative represents the first, and in many cases the only, step of the degradation mechanism. The photodegradation process causes the complete loss of pharmacological activity and may trigger the formation of single and superoxide oxygen species, potentially responsible for phototoxic reactions. Several analytical techniques have been proposed for DHP determination in the presence of their photoproducts. Nowadays, DHPs are all marketed in solid formulations, especially tablets, because photodegradation is particularly fast in solution. Various approaches aimed to protect molecular integrity and therapeutic activity of these drugs from the effects of light are currently studied. This review covers the studies over the last years about photodegradation of the DHPs and the approaches to obtain photostable formulations of these drugs.